Body vibration and its transmission in alpine ski racing - Fasel, B.; Lechot, C.; Spörri, J.; Müller, E.; Aminian, K. (14th International Symposium on 3D Analysis of Human Movement, 2016)
The aim of the study was to quantify the vibrations occurring at the lower limbs and the trunk during alpine ski racing. Four European Cup level athletes skied each three runs on a typical giant slalom course. For each turn, power spectral density (PSD) of the measured accelerations along the segment`s longitudinal axes was computed. Run-average PSD for each body segment and the PSD ratio between neighboring body segments were reported. With regard to the latter, results were consistent to previous studies analyzing the vibration transmission between different body segments when exposed to vibrating plates or shocks from the foot strike during running. Vibration transmission was nonlinear. The knee was attenuating 75% of the vibrations from 8-12Hz whereas the hip did not attenuate any vibration below 10Hz. The trunk attenuated frequencies below 10Hz but not between 10 and 25Hz. In future, the proposed method might help to better understand of the effects of body vibrations on muscle activation and balance/motion control, and might provide deeper insights of the cause and for the prevention of overuse injuries.